1988
DOI: 10.3133/pp1403c
|View full text |Cite
|
Sign up to set email alerts
|

Ground-water hydraulics, regional flow, and ground-water development of the Floridan aquifer system in Florida and in parts of Georgia, South Carolina, and Alabama

Abstract: The Regional Aquifer-System Analysis (RASA) Program was started in 1978 following a congressional mandate to develop quantitative appraisals of the major groundwater systems of the United States. The RASA Program represents a systematic effort to study a number of the Nation's most important aquifer systems, which in aggregate underlie much of the country and which represent an important component of the Nation's total water supply. In general, the boundaries of these studies are identified by the hydrologic e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
171
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(175 citation statements)
references
References 21 publications
4
171
0
Order By: Relevance
“…From the Polk City region, groundwater flows radially outward toward the coast in the largely confined Upper Floridan aquifer, discharging in the case of our studied flow path, to the Gulf of Mexico in the vicinity of Venice, Florida ( Fig. 1; Bush and Johnston 1988;Wicks and Herman 1994;Sacks et al 1995;Plummer and Sprinkle 2001;Haque and Johannesson 2006b). Along the studied flow path, the Upper Floridan aquifer is confined from below by the middle confining unit (dolomite with intergranular anhydrite and gypsum) and from above by the overlying Hawthorn Group (sands, marl, clay, limestone, dolostone, and phosphatic depostits; Wilson and Gerhart 1979;Miller 1986;Lamoreaux 1989;Sacks et al 1995;Plummer and Sprinkle 2001).…”
Section: Upper Floridan Aquifermentioning
confidence: 98%
“…From the Polk City region, groundwater flows radially outward toward the coast in the largely confined Upper Floridan aquifer, discharging in the case of our studied flow path, to the Gulf of Mexico in the vicinity of Venice, Florida ( Fig. 1; Bush and Johnston 1988;Wicks and Herman 1994;Sacks et al 1995;Plummer and Sprinkle 2001;Haque and Johannesson 2006b). Along the studied flow path, the Upper Floridan aquifer is confined from below by the middle confining unit (dolomite with intergranular anhydrite and gypsum) and from above by the overlying Hawthorn Group (sands, marl, clay, limestone, dolostone, and phosphatic depostits; Wilson and Gerhart 1979;Miller 1986;Lamoreaux 1989;Sacks et al 1995;Plummer and Sprinkle 2001).…”
Section: Upper Floridan Aquifermentioning
confidence: 98%
“…The porosity and permeability of the UFA varies greatly near springs, because voids in the limestone range from small solution openings to large cavernous openings and networks of conduits. The transmissivity of the UFA near springs ranges from 2800 to 1.1!10 6 m 2 day K1 (Bush and Johnson, 1988) and reflects the large variation in permeability. Hunter's, Tarpon Hole and Deering Estate spring are considered submarine springs that discharge mainly fresh water directly into coastal salt marshes.…”
Section: Sampling Locationsmentioning
confidence: 99%
“…Recharge to the unconfined UFA in this area ranges from 40 to 80 cm/year (15-31 in./year) (Grubbs, 1998) and is highly variable spatially and seasonally. Regional simulation of the groundwater flow system indicated that first-magnitude springs in this area receive only a very small amount of water from upward movement along deep regional flow paths originating in the lower part of the UFA (Bush and Johnston, 1988).…”
Section: Description Of Study Areamentioning
confidence: 98%